Analisis Persepsi Dosen dan Mahasiswa terhadap Penggunaan AI dalam Pembelajaran Bahasa dan Sastra Indonesia - Frieska Maryova Rachmasisca; Surastina Surastina (Lentera: Jurnal Ilmiah Kependidikan, 2025)
The development of digital technology has brought significant changes to higher education, including in the teaching of Indonesian Language and Literature. One emerging technology that is increasingly utilized in academic contexts is Artificial Intelligence (AI) as a learning support tool. This study aims to analyze lecturers’ and students’ perceptions of AI use in Indonesian Language and Literature learning and its implications for academic literacy development. The study is motivated by ongoing challenges in higher education, particularly regarding students’ academic writing skills, idea development, language accuracy, and active engagement in learning activities. A qualitative descriptive approach was employed, involving lecturers and students participating in Indonesian Language and Literature courses as research subjects. Data were collected through open-ended questionnaires, interviews, classroom observations, and documentation of students’ academic assignments. The findings indicate that both lecturers and students generally hold positive perceptions of AI as a supportive learning tool. AI is perceived to assist students in understanding academic text structures, improving language use, and enhancing confidence and learning autonomy. From the lecturers’ perspective, AI is considered a promising pedagogical innovation, yet it requires guidance and ethical oversight to ensure responsible use. The study concludes that integrating AI into Indonesian Language and Literature instruction offers significant potential for improving academic literacy, provided it is implemented in a planned, ethical, and responsible manner.